2005
DOI: 10.1105/tpc.105.030767
|View full text |Cite
|
Sign up to set email alerts
|

CINNAMYL ALCOHOL DEHYDROGENASE-C and -D Are the Primary Genes Involved in Lignin Biosynthesis in the Floral Stem of Arabidopsis

Abstract: During lignin biosynthesis in angiosperms, coniferyl and sinapyl aldehydes are believed to be converted into their corresponding alcohols by cinnamyl alcohol dehydrogenase (CAD) and by sinapyl alcohol dehydrogenase (SAD), respectively. This work clearly shows that CAD-C and CAD-D act as the primary genes involved in lignin biosynthesis in the floral stem of Arabidopsis thaliana by supplying both coniferyl and sinapyl alcohols. An Arabidopsis CAD double mutant (cad-c cad-d) resulted in a phenotype with a limp f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
347
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(376 citation statements)
references
References 76 publications
25
347
1
3
Order By: Relevance
“…Previous studies have indicated impairing different steps in monolignol biosynthesis results in reddish brown to tan stem and stalk pigmentation, including the CAD and COMT mutants examined in this study (Mackay et al 1997, Tsai et al 1998, Sibout et al 2005, Zhang et al 2006). There are differences in pith and midrib (leaf vein) coloration between bmr6 and bmr12 (Porter et al 1978, Saballos et al 2009), probably because bmr6 and bmr12 block different steps of the monolignol biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have indicated impairing different steps in monolignol biosynthesis results in reddish brown to tan stem and stalk pigmentation, including the CAD and COMT mutants examined in this study (Mackay et al 1997, Tsai et al 1998, Sibout et al 2005, Zhang et al 2006). There are differences in pith and midrib (leaf vein) coloration between bmr6 and bmr12 (Porter et al 1978, Saballos et al 2009), probably because bmr6 and bmr12 block different steps of the monolignol biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 73%
“…The dried cell wall materials were assayed for cellulose content with the anthrone reagent (Updegraff 1969) with Whatman 3MM paper as the standard (Whatman, Maidstone, UK). The determination of lignin content was performed on the extract-free samples using the standard Klason procedure (Sibout et al 2005). The evaluation of lignin structure was assayed using the DFRC protocol (Lu and Ralph 1997).…”
Section: Measurement Of Cell Wall Compositionmentioning
confidence: 99%
“…These components originate from the polymerization of the three monolignols, the p-coumaryl, coniferyl, and sinapyl alcohols, respectively (Sibout et al 2005). The types and amount of lignin units vary across plant species, tissues, cell types, and cell wall layers and are influenced by developmental and environmental factors (Campbell and Sederoff 1996;Donaldson 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations